2022
DOI: 10.3390/children9060845
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Stable Intramedullary Nailing for Treatment of Pediatric Tibial Fractures: A 20-Year Single Center Experience of 132 Cases

Abstract: Objective: The aim of this study was to analyze the outcomes and complications in children treated with elastic stable intramedullary nailing (ESIN) for tibial fractures. Methods: The study included 132 patients (92 males) with a median age of 11 years (IQR 10, 15) treated with ESIN for displaced tibial shaft fractures or dia-metaphyseal distal tibial fractures from March 2002 to March 2022. The median follow-up was 118.5 months (IQR 74.5, 170). The primary outcome was success rate, while secondary outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[10,17,25] However, as casting has been shown to be associated with poor radiographic outcomes, redisplacement in cast, and delayed return to activities, [12,26] ESIN and other options for surgical management, such as compression plating, have been proposed. Recent literature has provided evidence that ESIN can be used safely and effectively in distal and proximal diametaphyseal fractures of the and femur, [2,3,6,12,[15][16][17][18] but these studies have been limited by small sample sizes and have left unanswered the question of whether this technique can be used in the most distal and proximal fractures. The results of our study demonstrate that although radiographic outcomes after ESIN in short-segment fractures were inferior to those in distal or proximal third shaft fractures, clinical outcomes were no different, suggesting that ESIN can be considered as a management option in these difficult-to-treat fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,17,25] However, as casting has been shown to be associated with poor radiographic outcomes, redisplacement in cast, and delayed return to activities, [12,26] ESIN and other options for surgical management, such as compression plating, have been proposed. Recent literature has provided evidence that ESIN can be used safely and effectively in distal and proximal diametaphyseal fractures of the and femur, [2,3,6,12,[15][16][17][18] but these studies have been limited by small sample sizes and have left unanswered the question of whether this technique can be used in the most distal and proximal fractures. The results of our study demonstrate that although radiographic outcomes after ESIN in short-segment fractures were inferior to those in distal or proximal third shaft fractures, clinical outcomes were no different, suggesting that ESIN can be considered as a management option in these difficult-to-treat fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[14] In recent years, several studies have examined the use of ESIN in distal diametaphyseal fractures in the lower extremities. [2,3,6,12,[15][16][17][18] Although they have had small sample sizes, the studies have demonstrated that ESIN is a safe and effective surgical management option for these fractures. [2,3,6,12,[15][16][17][18] However, they have primarily included patients with fractures in the more proximal portions of the diametaphyseal region, and controversy remains over whether ESIN can be used for fixation of the most distal and proximal diametaphyseal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…In two studies [11,19] taking the diagnostic cut-off of 7 points will give 100% of the PPV, in our study, when changing the cut-off point to 6 points, it also gives 100% of the PPV. However, the recommendations still suggest that exploratory surgery is appropriate for suspected cases [2,3], so we still choose the cut-off point of 5 to avoid missing TT cases. Several factors need to be considered including the qualifications of the staff applying the points, population characteristics, context and available resources.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, TT requires early diagnosis and emergency surgical treatment. The salvage rates depend on the duration of pain, it can reach 97% if the operation is performed within 6 hours after symptoms onset and decrease to 60% if the time exceeds 12 hours [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large Croatian study describes the results of an impressive number of 132 pediatric tibial fractures treated with elastic stable intramedullary fixation during a period of 20 years [ 21 ]. Fifteen complications occurred, of which six required reoperation due to the secondary angulation of the fracture.…”
mentioning
confidence: 99%